Self-Embedded Foreign Bodies in the Lower Urinary Tract - Narendra Pai; Suraj Hegde; T. P. Rajeev; Amit Kumar (Current Topics in Medicine and Medical Research Vol. 12, 2021)
In daily practice, we encounter many patients with calculi in various part of the urinary tract. However, it is rarely a peculiar foreign body such as clips, pins, electric wires and coins are found which masquerades as a calculus. Such patients often have associated psychiatric or sexual illnesses with autoeroticism which compels them to insert such foreign objects into the urinary tract. These can be extracted by an endoscopic approach usually, but seldom open approach may be required. A strong male predominance is observed in cases with self insertion of foreign bodies into the urinary tract.